The present and the future: Strategic partnering to support MSLs - Dr Abhishek Arvind Kurne, Dr Shambhu Bimal Mandal Subject Matter Expert (International Journal of Scientific Research and Management (IJSRM), 2017)
A study published in 2012 analyzed more than three dozen drug and device companies’ Medical ScienceLiaison (MSL) operations around the world. The study revealed that the top 20 pharmaceutical organizationsinvest between $10 million and $48 million to deploy MSLs in the US, Europe and Asia.